Audiovisual Translation and Media Accessibility Training in the EMT Network - Valdez, Susana; Secara, Alina; Perez, Emília; Bywood, Lindsay (Journal of Audiovisual Translation, 2023)
The increase in demand for the localisation of audiovisual media content has led to increased incorporation of audiovisual translation and accessibility modules into university curricula in many regions (Bolaños-García-Escribano et al., 2021). This study aims to map part of the audiovisual translation (AVT) and media accessibility (MA) training landscape in Europe, presenting the findings of the 2020 Audiovisual Translation and Media Accessibility Training Survey conducted among the European Master’s in Translation network. It reflects on the results obtained from 55 European Master’s programmes focused on the training of future translators and shows that the majority provide AVT and some MA training, mainly within broad AVT modules and, to a much lesser extent, in dedicated compulsory modules. The insights gained from this study are relevant to establishing a benchmark that will make it possible to track any developments in the teaching of AVT and MA in the EMT network and beyond. Lay summary In recent years, the need to translate audiovisual content for speakers of other languages and to make it accessible to those with disabilities has increased. This has led to growth in courses in audiovisual translation and accessibility in university programs in many parts of the world. Because of this, we wanted to understand the current situation with regards to audiovisual translation and media accessibility training in Europe. To do so, we conducted a survey focusing on European Master's programs in translation. We focused on programs that belong to the European Master's in Translation network. This network is a partnership between the European Commission's Translation Department and universities. It's a quality stamp for Master's translation programs that meet the high standards of the European Commission's Translation Department. We used a survey to collect data from 55 European Master's programs. We discovered that most of these programs offered some level of training in audiovisual translation, and some of them also trained students in media accessibility (for people with disabilities). Audiovisual translation was mostly taught in more general modules, and media accessibility was less common and was often part of optional modules. We now also understand better what is taught, the extent to which practical and theoretical training in this field is offered, the main working languages, the tools used, and to what extent the programs cooperate with industry professionals. So, why is this study important? It helps us better understand the current status of audiovisual translation and media accessibility education in Europe. By studying these Master's programs, we have created a starting point for tracking future changes in audiovisual translation and media accessibility training in the European Master's in Translation network and beyond. This information is important for educators and policymakers who want to improve existing opportunities and offer more training in audiovisual translation and accessibility. In summary, this research sheds light on how audiovisual translation and media accessibility are taught in European Master's programs. It highlights the need for more structured and comprehensive training in these areas to meet the growing demand for accessible audiovisual content.